The synthesis, characterization and conductance studies of new Cu(II), Ni(II) and Zn(II) complexes with the Schiff base derived from 1,2-bis-(o-aminophenoxy)ethane and salicylaldehyde - Temel, H; Çakir, Ü; Ugras, HI; Sekerci, M (Taylor & Francis Ltd, 2003)
Cu(II), Ni(II) and Zn(II) complexes with the Schiff base derived from 1,2-bis-(omicron-aminophenoxy)ethane with salicylaidehyde have been prepared. The complexes have been characterized by elemental analysis, magnetic measurements, H-1 NMR, C NMR, UV, visible and IR spectra as well as conductance measurements. The ligand is coordinated to the central metal as a tetradentate ONNO ligand. The four bonding sites are the central azomethine nitrogen and aldehydic OH groups. The ligand was used for complexation studies. Stability constants were measured by a conductometric method. Furthermore, the stability constants for complexation between ZnCl2 and Cu(NO3)(2) salts and N,N'-bis(salicylidene)-1,2-bis-(omicron-aminophenoxy)-ethane (H2L) in 80% dioxane/water and pure methanol were determined from conductance measurements. The magnitudes of these ion association constants are related to the nature of the solvation of the cation and the complexed cation. The mobilities of the complexes are also dependent, in part, upon solvation effects.
Keywords: Schiff base; Cu(II); Ni(II) and Zn(II) complexes; stability constants